Kształtowanie się stabilizującej reguły wydatkowej oraz mechanizm jej działania - Ostrowski, Michał (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2019)
In the introduction, the paper defines the concept of expenditure rules and describes its role in maintaining the modernly understood fiscal sustainability. Notion of an efficient expenditure rule is characterized. Then, there is a briefly description of all expenditure rules that had been used in the Republic of Poland till the adoption of the stabilizing expenditure rule, which is the key topic in this article. There are pointed out assumptions which the stabilizing expenditure rule was supposed to implement. Its original construction is described in the comprehensive way. However, neither the rule’s mechanism evaluation or its functioning in the practice is not presented in this paper. These matters will be touched on in the following paper which will continue the topic of stabilizing expenditure rule.
Keywords: stabilizing expenditure rule; state budget; public finance sector; deficit bias; fiscal sustainability